Long-Term Boron-Excess-Induced Alterations of Gene Profiles in Roots of Two Citrus Species Differing in Boron-Tolerance Revealed by cDNA-AFLP - Guo, Peng; Qi, Yi-Ping; Yang, Lin-Tong; Ye, Xin; Huang, Jing-Hao; Chen, Li-Song (Frontiers in Plant Science, 2016)
Boron (B) toxicity is observed in some citrus orchards in China. However, limited data are available on the molecular mechanisms of citrus B-toxicity and B-tolerance. Using cDNA-AFLP, we identified 20 up- and 52 down-regulated genes, and 44 up- and 66 down-regulated genes from excess B-treated Citrus sinensis and Citrus grandis roots, respectively, thereby demonstrating that gene expression profiles were more affected in the latter. In addition, phosphorus and total soluble protein concentrations were lowered only in excess B-treated C. grandis roots. Apparently, C. sinensis had higher B-tolerance than C. grandis. Our results suggested that the following several aspects were responsible for the difference in the B-tolerance between the two citrus species including: (a) B-excess induced Root Hair Defective 3 expression in C. sinensis roots, and repressed villin4 expression in C. grandis roots; accordingly, root growth was less inhibited by B-excess in the former; (b) antioxidant systems were impaired in excess B-treated C. grandis roots, hence accelerating root senescence; (c) genes related to Ca2+ signals were inhibited (induced) by B-excess in C. grandis (C. sinensis) roots. B-excess-responsive genes related to energy (i.e., alternative oxidase and cytochrome P450), lipid (i.e., Glycerol-3-phosphate acyltransferase 9 and citrus dioxygenase), and nucleic acid (i.e., HDA19, histone 4, and ribonucleotide reductase RNR1 like protein) metabolisms also possibly accounted for the difference in the B-tolerance between the two citrus species. These data increased our understanding of the mechanisms on citrus B-toxicity and B-tolerance at transcriptional level.